Experimental Investigation of the Reflection Characteristics of a Flat Lunar Surface - Lu, Feng; Yamaguchi, Akira; Takeuchi, Kazunori; Shinbo, Hiroyuki (IEEE International Conference on Wireless for Space and Extreme Environments conference digest (Online), 2022)
The knowledge and characterization of radio propagation is important for a wireless communication system as it is key to the design of the coverage area of the system's base station. Since the lunar surface is covered by a soil-like regolith layer, which includes more metal compounds than the surface soil on Earth, radio propagation on the lunar surface may be different from that on Earth. To assess radio propagation at the lunar surface, the authors measured the reflection coefficients of a regolith simulant (a simulated lunar soil) at several frequencies used by mobile communication systems. The results of the experiments show that the flat ground reflection characteristics on the Moon are similar to those on Earth.